THE CONCEPT OF HUMANIS-RELIGIUS EDUCATION IN EARLY AGE CHILDREN - M Fadlillah (Universitas Muhammadiyah Ponorogo, 2019)
The big problem of Indonesian people today is moral degradation. The number of criminal cases, promiscuity, drugs, and corruption indicate that the moral of this nation has been damaged. If it is not immediately addressed, it will have a negative impact on the sustainability of the nation . To overcome moral degradation, one way that is considered very effective is to implement religious humanist education from an early age. that in those days the child is very easy to receive new information and has not been affected by negative behavior from outside. Religious Humanist Education (RHE) is very important for early childhood. RHE teaches children about morality and good values towards fellow human beings and the environment. RHE can grow children to be intelligent, to have character, and to be noble. Therefore, this article aimed to examine the concept of religious humanist education in early childhood.